Meaning transfer in celebrity endorsements: an explanation using metaphors. Issue 8 (17th November 2018) - Roy, Subhadip
Abstract: The concept of meaning transfer is relevant in the context of celebrity endorsements but rarely tested because of its complexity. This study integrates the basic tenets of meaning transfer model in celebrity endorsements and metaphor theory in marketing. The study builds on the literature on the various streams in celebrity endorsements and notes the contradictions in each. Thereby, it presents a conceptual model of meaning transfer using metaphors as the explaining thread. The model is validated using empirical data collected through a metaphor elicitation method. Based on the results, four propositions are developed related to celebrity metaphors and metaphor transfer in celebrity endorsements. The findings suggest that celebrity meaning(s) could be explained through metaphors and the metaphors may be transferred to a brand from a celebrity endorser via an endorsement. The propositions developed in the study have important implications for researchers and practitioners in celebrity endorsement.